A Política Estadual de Produção Agroecológica e Orgânica (PEAPO) do Espírito Santo: um olhar sobre a realidade social, econômica e política do Estado - Tavares, Teyliana Ribett (2023)
The State Policy for Agroecological and Organic Production (PEAPO) of Espírito Santo, established in 2018, is the most recent achievement of the state's agroecological movement. The present work has the general objective of analyzing PEAPO-ES, verifying the articulation between the ecological dimensions and productive techniques, social, cultural, economic and political aspects of agroecology, and the implementation and configuration of this policy by the government of the state of Espírito Santo, with a view to a Identify limits and possibilities for expanding transition processes to more sustainable agriculture based on said policy. Through specific objectives, we seek to identify how the articulation of the dimensions of agroecology is manifested in the structure of PEAPO-ES and its implementation and management instruments; reflection on the contribution of public policies involving agroecology to the dissemination of agroecological transition processes; identify the configuration and scope of guaranteed rights, access criteria and forms of articulation with other state economic and social policies; verify the configuration of financing and spending carried out by the state government with PEAPO-ES, not referring to the direction and amount of spending; and, characterize the management and democratic control of PEAPO. Considering that the State Plan for Agroecological and Organic Production (PLEAPO) is the main instrument for implementing PEAPO-ES and the State Council for Sustainable Rural Development (CEDRS) and the Organic Production Commission (CPOrg) are the policy management instruments, we used the following documents for analysis: PLEAPO I; the minutes of CEDRS-ES meetings that took place after the policy was instituted until 2022; and the CPOrg-ES memories of meetings held until September 2023. The following were also used as documents for analysis: the third Strategic Plan for the Development of Agriculture in Espírito Santo (PEDEAG 3); the Multi-Year Plan (PPA) 2020-2023; and, the Programmatic Execution Reports of the Government of the State of Espírito Santo for 2020, 2021 and 2022. Based on bibliographies that contained the debate on the historical formation of Espírito Santo, articulated with the social and economic dimensions of the process, we point out characteristics that forged the structure state land, and which, according to the premises of agroecology presented in the literature that conceptualizes the topic, must be considered in the development of public policies that promote transition processes to more sustainable agriculture. The trajectory of agroecology in Brazil and Espírito Santo was presented as a way of helping to understand the concept, the process that culminated in the establishment of PEAPO-ES and the reality that arises for the implementation of the policy. We identified that the construction of PEAPO-ES results from a historical process of organization and struggle by governmental and non-governmental actors who practice organic agriculture and promote agroecology in the state. After the institution of the policy, the search for its implementation comes up against the lack of budget and the unavailability of professionals destined to execute the policy by the state government, with the main indication of this unwillingness being the political orientation of the current management focused strictly on agribusiness.